2020
DOI: 10.1186/s12885-020-6644-7
|View full text |Cite
|
Sign up to set email alerts
|

Silica and asbestos exposure at work and the risk of bladder cancer in Canadian men: a population-based case-control study

Abstract: Background: Silica and asbestos are recognized lung carcinogens. However, their role in carcinogenesis at other organs is less clear. Clearance of inhaled silica particles and asbestos fibers from the lungs may lead to translocation to sites such as the bladder where they may initiate carcinogenesis. We used data from a Canadian populationbased case-control study to evaluate the associations between these workplace exposures and bladder cancer. Methods: Data from a population-based case-control study were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
0
6
0
2
Order By: Relevance
“…Outras neoplasias decorrentes da exposição ao asbesto são bucais, de faringe, de esôfago, de fígado e de ducto biliar, sendo a mortalidade por essas causas verificada em trabalhadores manuais da indústria de asbesto, seguidos dos setores automobilístico, naval e construção civil 21,22 . Essa circunstância comprova o potencial cancerígeno das fibras 51,52 .…”
Section: Discussionunclassified
“…Outras neoplasias decorrentes da exposição ao asbesto são bucais, de faringe, de esôfago, de fígado e de ducto biliar, sendo a mortalidade por essas causas verificada em trabalhadores manuais da indústria de asbesto, seguidos dos setores automobilístico, naval e construção civil 21,22 . Essa circunstância comprova o potencial cancerígeno das fibras 51,52 .…”
Section: Discussionunclassified
“…Majority of the studies are cohort ones, but there are also case-control studies carried out all over the world. The research has focused primarily on assessing the risk of developing BCa [31][32][33][34][35][36], but also overall survival rates [37], overall incidence [38], mortality odds ratio [32,39,40] and lifetime prevalence [41,42]. Most of the studies have found an increased risk of developing BCa among exposed workers.…”
Section: Occupational Exposurementioning
confidence: 99%
“…Moreover, numerous cases of BCa are observed among workers working in the dying process. This is because of Different types of work silica, asbestos Canada [33] Painters and rubber manufacturing industry painting, trichloroethylene, asbestos, wood dust, diesel gasoline exhausts, formaldehyde, and painting or varnish)…”
Section: Occupational Exposurementioning
confidence: 99%
“…Figure 2 shows the geographical distribution of studies worldwide. Eight studies were conducted in France (21)(22)(23)(24)(25)(26)(27)(28) and Canada (29)(30)(31)(32)(33)(34)(35)(36). There were also 4 papers in Germany (37)(38)(39)(40), and 3 in Finland (41)(42)(43).…”
Section: The Geographical Diversity Of Studies Conducted Worldwidementioning
confidence: 99%
“…The effect of diesel motor exhausts (DME) was investigated in 5 studies (27,33,37,40,47). Silica and/or asbestos (31,49) polycyclic aromatic hydrocarbons (PAH), and/or aromatic amines (39,65) were examined in 2 studies. Furthermore, 2 studies examined metalworking fluids (MWFs) (23,51).…”
Section: The Types Of Occupational Carcinogensmentioning
confidence: 99%